Transparent TiO2 nanotubes supporting silver sulfide for photoelectrochemical water splitting - Lipińska, Wiktoria; Wolff, Stefania; Dehm, Katharina; Hager, Simon; Gumieniak, Justyna; Kramek, Agnieszka; Crisp, Ryan; Coy, Emerson; Grochowska, Katarzyna; Siuzdak, Katarzyna (Nanoscale, 2024)
Differences between photoelectrochemical and electrochemical activity were thoroughly investigated for the oxygen evolution reaction mediated by Ag2S deposited on two types of ordered titania substrates. Titanium dioxide nanotubes were fabricated by anodization of magnetron sputtered Ti films on ITO-coated glass substrates or directly from Ti foil. Further, Ag2S deposition on the nanotubes was carried out using successive ionic layer adsorption and reaction, known as SILAR, with 5, 25, and 45 cycles performed. Two types of nanotubes, one on transparent the other on non-transparent substrates were compared regarding their geometry, structure, optical, and electrochemical properties. It was demonstrated that the composite of Ag2S grown on transparent nanotubes exhibits higher catalytic activity compared to Ag2S grown on the nanotubes formed on Ti foil. The results showed that transparent nanotubes after modification with Ag2S by 25 SILAR cycles exhibit ca. 3 times higher photocurrent under visible light illumination than non-transparent ones treated with the same number of cycles. Furthermore, transparent nanotubes after 45 SILAR cycles of Ag2S exhibit enhanced activity towards oxygen evolution reaction with 9.3 mA cm−2 at 1.1 V vs. Ag/AgCl/0.1 M KCl which is six times higher than titania alone on Ti foil.
CRIS-Team Scopus Importer:2024-08-09